Prevention and Decontamination of Chemical, Biological, Radiological, and Nuclear Contaminants for the Emergency Medical Personnel during Ambulance Services - Shin, Dong Min (Hanyang medical reviews, 2015)
This paper will review proper protocol for Emergency Medical Technicians (EMTs) between the ambulance station, scene and hospital. EMTs must know how to protect themselves both inside and outside the ambulance from chemical, biological, radiological, and nuclear (CBRN) contaminants in order to provide the best quality care. EMTs should also know how to remove contamination after taking a patient to the hospital. A CBRN protocol at the scene of exposure is the best defense strategy for protecting both EMTs and the emergency ambulance vehicle from contamination. If EMTs and the emergency ambulance vehicle are exposed to CBRN, neither will be of great service as they both play a critical part in the quality of care given to a patient. In the event of possible exposure, EMTs should dress in high perceptibility personal protective equipment (PPE). Those who have been trained prior should arrive to the scene with an air purifying respirator. Before a patient with possible exposure is placed inside an emergency ambulance vehicle, all patients’ compartments should be completely covered and sealed with plastic film. Once the emergency medical crew reaches the hospital and the patient is discharged from the emergency vehicle, all plastic film inside the ambulance, from the cockpit ceiling to the floor, should be removed and properly discarded. The patient’s clothing and shoes should be placed into a double layered plastic bag. Adhering to proper protocols, within 10 minutes of arrival at hospital, a contaminated ambulance should undergo pre-washing, decontamination and rinsing operations. KCI Citation Count: 1